Response of alfalfa (Medicago sativa L.) to diurnal and nocturnal saline sprinkler irrigations. I: total dry matter and hay quality - Isla, R; Aragüés, R (Irrigation science, 2009)
Little information is available on the quantitative effects on crops of saline sprinkler irrigations and the presumable beneficial effects of nocturnal versus diurnal irrigations. We measured crude protein content, carbon isotope discrimination and total dry matter (TDM) of alfalfa (Medicago sativa L.) subject to diurnal and nocturnal saline sprinkler irrigations. The work was carried out in Zaragoza (Spain) during the 2004-2006 growing seasons with a triple line source sprinkler system using synthetic saline waters dominated by NaCl with an irrigation water EC ranging from 0.5 to 5.6 dS m⁻¹. The quality of alfalfa hay assessed through its crude protein concentration was not significantly affected by salinity. Carbon isotope discrimination, an indicator of the effect of osmotic stress on plant water status, tended to decrease with increases in salinity. Based on a piecewise linear response model, alfalfa grown under saline sprinkler irrigation was shown to be more tolerant (threshold soil salinity, ECe = 3.5 dS m⁻¹) than in previous experiments under surface irrigation (threshold ECe = 2.0 dS m⁻¹) at relatively low salinity values, but became more sensitive at higher salinity values as shown by the higher absolute slope (13.4%) for sprinkler as compared to surface irrigation (7.3%). No significant differences in TDM were found between diurnal and nocturnal saline sprinkler irrigations. The recommended practice of irrigating at night for sprinkler irrigation using saline water is therefore not supported by our results in alfalfa grown under semiarid conditions.